(untitled) (Perner’s Contacts, 2019)
Railway transport and its reforms are currently a much-debated topic. The state began to realize the importance of rail transport and began to address operationally the issue of rail transport, which was underestimated in the past and began to decline as a result of the expansion of road transport. Creating a competitive environment is one of the basic aspects of the efficient functioning of rail transport. The main aim of the paper is to analyze three selected railway companies providing public passenger transport on the Košice - Prague route in both directions on the basis of a comparison using the method of measuring the quality of services according to customer satisfaction (SERVQUAL). For the analysis, I chose three railway companies, namely Regiojet, Plc, Leo Express, Plc. Železniční společnost Slovensko, Plc. The result of the paper is to find out which of the examined companies is the most advantageous in terms of transport on the way Košice - Prague based on the quality of services provided.